Local variations in sawlog- and sawn product quality : sawing study of Norway spruce (Picea abies) and Scots pine (Pinus sylvestris) at a sawmill in central Sweden - Shimizu Nilsson, Megumi (SLU/School for Forest Management, 2011)
Factors associated with raw materials are one of the most important keys to success among sawmill industries today. A common opinion is that the potential for further development for wooden industries lies in improved integration between different part of the so called « wood-flow chain ». This project was carried out on request of a sawmills- and trading group company in central Sweden and Estonia as a part of the requirement for a Bachelor of Science degrees in forest management at Swedish University of Agricultural Sciences (SLU). The aim of the project was to investigate how geographical and topographical variations in a particular saw mill’s catchment area affect saw timber production of Norway spruce (Picea abies) and Scots pine (Pinus sylvestris). The study area corresponds to the latitude ranges of approximately 59o to 61oN, the longitude from 14o to 19oE and altitude above sea level from 5 to 550 m. A total of about 25 000 sawlogs was collected for the experiment during June 2010. Control measurements on sample logs, visual grading at the log sorting station and test sawing were performed. The results revealed significant geographical variations within the catchments’ area regarding timber quality of pine timber, however less obvious differences were found regarding spruce. It was also found that there is a stronger correlation between quality of the raw materials and the yield of sawn products for pine, however weaker or no correlation for spruce, which could be explained by the raw materials’ localization. The results of this study will be used to help making decisions about future utilization of raw materials from the end user’s point of view.